Bushman Letters/Bushman Literature Usable and Unusable Pasts. Issue 2 (3rd July 2021) - Chapman, Michael
Abstract : In remembrance of Michael Wessels This article avers that just as Bleek and Lloyd's research on 'Bushman voices' has the potential to enrich South African literature so does Wessels's study, Bushman Letters: Interpreting |Xam Narrative . A meta-critical account of 'Bushman Studies', Wessels provokes discussion on what might constitute Bushman expression, where and when it arose, how it has travelled to us, and what it might mean. Is it 'usable'? The question, in turn, raises contention about the translation of the oral voice, appropriation, and the reworking of texts. Is Bushman expression confined to a locality or has it a wider purchase? Wessels invokes a range of response from Propp's morphology of folktale to Derrida's metaphysics of presence. My literary history, Southern African Literatures, begins with "Bushman (San) Songs and Stories". In the light of this, I acknowledge Michael Wessels's contribution to literary studies.